Pengaruh Media Pembelajaran Flash Card Terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 SDN Tambak Kemerakan (International Forum of Researchers and Lecturers, 2023)
This study aims to determine whether or not there is an effect of using flash card learning media on the initial reading ability of grade 1 students at SDN Tambak Kemerakan. This type of research is a quantitative method of quasi-experimental design with nonequivalent control group design techniques. The sample in this research was all 51 students in class 1 at SDN Tambak Kemerakan. The results showed that there was a significant effect of flash card learning media on initial reading ability based on a significance value (2-tailed) obtained of 0.032 which when compared to the significance level was 0.032 <0.05, then the decision was Ha accepted which means that there is a difference significant effect on the application of flash card learning media on the initial reading ability of grade 1 students. Based on these calculations it can be concluded that there is a significant effect on the application of flash card learning media on the initial reading ability of grade 1 students at SDN Tambak Kemerakan